Isolation, Biochemical and Genomic Characterization of Glyphosate Tolerant Bacteria to Perform Microbe-Assisted Phytoremediation - Massot, Francisco (2021)
The large-scale use of the herbicide glyphosate leads to growing ecotoxicological and human health concerns. Microbe-assisted phytoremediation arises as a good option to remove, contain, or degrade glyphosate from soils and waterbodies, and thus avoid further spreading to non-target areas. To achieve this, availability of plant-colonizing, glyphosate-tolerant and -degrading strains is required and at the same time, it must be linked to plant-microorganism interaction studies focusing on a substantive ability to colonize the roots and degrade or transform the herbicide. In this work, we isolated bacteria from a chronically glyphosate-exposed site in Argentina, evaluated their glyphosate tolerance using the minimum inhibitory concentration assay, their in vitro degradation potential, their plant growth-promotion traits, and performed whole genome sequencing to gain insight into the application of a phytoremediation strategy to remediate glyphosate contaminated agronomic soils. Twenty-four soil and root-associated bacterial strains were isolated. Sixteen could grow using glyphosate as the sole source of phosphorous. As shown in MIC assay, some strains tolerated up to 10000 mg kg–1 of glyphosate. Most of them also demonstrated a diverse spectrum of in vitro plant growth-promotion traits, confirmed in their genome sequences. Two representative isolates were studied for their root colonization. An isolate of Ochrobactrum haematophilum exhibited different colonization patterns in the rhizoplane compared to an isolate of Rhizobium sp. Both strains were able to metabolize almost 50% of the original glyphosate concentration of 50 mg l–1 in 9 days. In a microcosms experiment with Lotus corniculatus L, O. haematophilum performed better than Rhizobium, with 97% of glyphosate transformed after 20 days. The results suggest that L. corniculatus in combination with to O. haematophilum can be adopted for phytoremediation of glyphosate on agricultural soils. An effective strategy is presented of linking the experimental data from the isolation of tolerant bacteria with performing plant-bacteria interaction tests to demonstrate positive effects on the removal of glyphosate from soils.